Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1001/jama.2018.21362
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnetic Resonance Imaging vs Conventional Treat-to-Target Strategies on Disease Activity Remission and Radiographic Progression in Rheumatoid Arthritis

Abstract: IMPORTANCE Whether using magnetic resonance imaging (MRI) to guide treatment in patients with rheumatoid arthritis (RA) improves disease activity and slows joint damage progression is unknown. OBJECTIVE To determine whether an MRI-guided treat-to-target strategy vs a conventional clinical treat-to-target strategy improves outcomes in patients with RA in clinical remission. DESIGN, SETTING, AND PARTICIPANTS Two-year, randomized, multicenter trial conducted at 9 hospitals in Denmark. Two hundred patients with RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
1
4

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 37 publications
0
55
1
4
Order By: Relevance
“…Further, studies on tapering and stopping treatment broaden the information base for rheumatologists and patients on the question of possible disease flares after tapering or cessation of drugs, once patients have reached the clinical target. Strategic studies on how to optimally treat patients to target,5 using clinical and imaging targets have also answered important research questions 6. Finally, a large number of trials compared the efficacy and safety of biosimilars (bs) DMARDs with those of their bio-originators (bo), including switching between boDMARD and respective bsDMARDs.…”
Section: Introductionmentioning
confidence: 99%
“…Further, studies on tapering and stopping treatment broaden the information base for rheumatologists and patients on the question of possible disease flares after tapering or cessation of drugs, once patients have reached the clinical target. Strategic studies on how to optimally treat patients to target,5 using clinical and imaging targets have also answered important research questions 6. Finally, a large number of trials compared the efficacy and safety of biosimilars (bs) DMARDs with those of their bio-originators (bo), including switching between boDMARD and respective bsDMARDs.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, achieving US remission and the complete abrogation of subclinical activity should be the ultimate goal for our RA patients. However, recent data from TASER [17], ARTIC [29] and IMAGINE-RA [30] trials showed that speci cally targeting subclinical in ammation did not yield better clinical outcomes. This target could imply a risk of overtreating, with a higher use of biological therapy and more adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the utility of MRI-demonstrated BME and PD-revealed articular synovitis, the roles of MRI and US monitoring for patients with RA in clinical settings have been controversial. In the IMAGINE-RA study of MRI, the use of MRI for treatment guidance did not improve the rate of disease activity remission or that of radiographic progression compared to a conventional treat-to-target (T2T) strategy [20]. In the TaSER study and the ARCTIC study of ultrasound, compared to clinical evaluations, the use of US for monitoring a cohort of early and active RA patients did not result in a higher frequency of patients in remission [21,22].…”
Section: Introductionmentioning
confidence: 99%